Narrativas indígenas y territorios amazónicos: una revisión crítica de los conceptos y las metodologías de la literatura académica - Angulo-Giraldo, Miguel (2025)
Recent studies on Indigenous literature have explored various concepts to recognize the diverse expressions of Indigenous communities' lives. These approaches aim to represent Indigenous experiences more accurately, traditionally examined through their oral and written literatures, within the context of the growing revaluation of Indigenous territories from political, literary, and social perspectives. The connection between Indigenous territories and narratives extends beyond memories, dreams, and collective stories, also influencing the everyday bodily experiences of individuals in their territorial existence. The purpose of this research is to identify the concepts and methodologies in academic literature that link the various Amazonian territories and Indigenous narratives. To achieve this, a narrative review of 50 articles published in the Scopus, SciELO, and Dimensions databases, relating to territories and Indigenous narratives from the past five years (2019-2024), was conducted. The main results show a diversity of concepts related to indigenous literature such as oralitegrafía, oralitura, oral narration, oral literature, among others. The study concludes that Indigenous narratives related to the Amazonian territory recount the community’s past, its process of inhabiting social space up to the present, and explain the diverse ways of relating to and from it, thus materializing the Amazonian life experience of Indigenous peoples.